`I don`t think they realise how good we are`: Innovation, inclusion and exclusion in women`s Olympic boxing - Tjønndal, A. (International Review for the Sociology of Sport, 2019)
Marginalisation and exclusion of women in elite boxing has emerged as a substantial international problem, threatening women`s democratic right to equal participation in sport. Since the London 2012 Olympic Games women`s boxing has been an Olympic event. However, only 3 of the 10 weight categories were included in the Olympic programme for women. Today, male boxers compete in 10 out of 10 possible weight categories. While female boxers have gained accessed to a previously closed realm, discrimination, exclusion and unequal treatment of female athletes remains a widespread problem in international elite boxing. This article explores how the introduction of women`s boxing into the Olympic Games involves practices of inclusion and exclusion in elite boxing. In particular, this analysis focuses on the following two research questions: (a) how practices of social exclusion and inclusion affect the involvement and engagement of women in boxing; and (b) how, and in what ways, female boxers have experienced recognition and acceptance in elite boxing after the introduction of women`s boxing into the Olympic Games. Using a qualitative approach including document analysis of official press releases from the International Olympic Committee (IOC) and the International Boxing Association (AIBA), as well as interviews with athletes and coaches, this study reveals that although women`s boxing has gained access to the Olympics, the structural and cultural changes that comprise the social inclusion of women in boxing are yet to be implemented.